The financial performance of Islamic boarding school in the domain of social networking, trust, and morality of financial accountability - Setyo Budi Hartono; Riska Wijayanti; Vella Rizki Sekarsari (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - The purpose of this study was to examine the effect of social capital and Morality of Financial Accountability (MoFA) on the financial performance of modern Islamic boarding schools.Method - The population of this research is Islamic boarding schools in Central Java with 40 samples. Measurements were made using a questionnaire with indicators contained in the variables of social networks, trust, MoFA, and financial performance. Data processing was carried out using WarpPLS software with small sample .Result - The results of this study are social network and trust variables have a significant and positive effect on financial performance with an influence value of 23% and 33% respectively. Meanwhile, if it is moderated by spiritual capital, it has an influence on the relationship between social network variables and trust on financial performance, respectively 28% and 21%. Thus spiritual capital will strengthen the relationship between social networks and trust.Implication - The relationship between MoFA in social capital can strengthen the financial performance of Islamic boarding schools due to additional information about plans to use donated funds for good.Originality - MoFA is the development of additional information on the basis of compilation on the legality of kindness, disclosure of consistent reports, honesty in transactions.